Landasan Fılosofıs Dan Analısıs Teorı Belajar Dalam Implementası Kurıkulum Merdeka Dı Sekolah Dasar - Roby Zulkarnain Noer; Deni Mustopa; Rizal Arizaldy Ramly; Mochamad Nursalim; Fajar Arianto (Elementary Teacher Education Program, Majalengka University, 2023)
Education is an important need for human life, every individual has the same right to receive educational services. Implementing an independent curriculum requires independent curriculum planning, philosophical values such as humanism, progressivism and constructivism can be implemented to create learning that is more relevant, interactive and respects the uniqueness and potential of students. The method used in writing and preparing this article is literature study. The results of this literature review are related to the philosophical basis and analysis of learning theory in implementing the independent curriculum. In implementing the Merdeka Curriculum, teachers also have an important role in recognizing students' potential, creating relevant learning, and implementing fun learning through a project-based approach, integrating relevant educational philosophies and the principles of the Merdeka Curriculum, it is hoped that learning can become more meaningful , according to the needs of students, and prepare them with relevant skills to face future challenges.